Feedback in Automated Clutch Control Circuit for Truck Start-Up Process - Le Van Nghia (Наука и техника)
The paper presents description of a mechatronic control system for mechanical transmission of a 20-ton truck, as well as its adaptive start-up algorithm, transient process behavior which significantly affects durability of automated power unit elements, vehicle movement smoothness and driver’s comfort when driving. A multidisciplinary model of the mechatronic control system has been developed in the software package Imagine Lab AMESim because its power unit including a diesel engine, a dry frictional two-disc clutch, a main mechanical stepped gearbox and an additional gearbox has electrical components besides mechanical and pneumatic ones. The given model allows to test complex control algorithms and analyze the behavior of intelligent systems in the early designing stages. The research has been carried out on the basis of the test complex at Department “Automobiles”, Automotive and Tractor Faculty, Belarusian National Technical University. Research results confirm an adequacy of the AMESim developed multidisciplinary model. Feedback on the increment of an angular velocity difference between driving and driven parts of the friction clutch has been introduced for precise friction clutch control. Threshold values of a feedback parameter have been determined on the basis of the developed computer model and these values will be used for programming a microprocessor unit when implementing an adaptive algorithm for a truck start-up process